A new mathematical model of wrist pulse waveforms characterizes patients with cardiovascular disease – A pilot study. (October 2017) - He, Dianning; Wang, Lu; Fan, Xiaobing; Yao, Yang; Geng, Ning; Sun, Yingxian; Xu, Lisheng; Qian, Wei
Abstract: The purpose of this study was to analyze and compare a series of measured radial pulse waves as a function of contact pressure for young and old healthy volunteers, and old patients with cardiovascular disease. The radial pulse waves were detected with a pressure sensor and the contact pressure of the sensor was incremented by 20 gf during the signal acquisition. A mathematical model of radial pulse waveform was developed by using two Gaussian functions modulated by radical functions and used to fit the pulse waveforms. Then, a ratio of area ( rA ) and a ratio of peak height ( rPH ) between percussion wave and dicrotic wave as a function of contact pressure were calculated based on fitted parameters. The results demonstrated that there was a maximum for waveform peak height, a minimum for rA ( r A m i n ) and a minimum for rPH ( r P H m i n ) appeared as contact pressure varied. On average, older patients had higher peak amplitude and a significantly smaller r A m i n ( p  < 0.001) and r P H m i n ( p  < 0.02) than the young and old volunteers. The r A m i n and r P H m i n calculated with the mathematical model had moderate to strong positive linear correlations ( r  = 0.66 to 0.84, p  < 0.006) with those directly calculated without the model. The receiver operating characteristic (ROC) analysis showed that the r A m i n calculated with the model and the contact pressure measured at the r A m i n had good diagnostic accuracy to distinguish healthy volunteers vs. diseased patients. Therefore, using the mathematical model to quantitatively analyze the radial pulse waveforms as a function of contact pressure could be useful in the diagnosis of cardiovascular diseases.